Synthesis, Antibacterial and Insecticidal Activities of Novel Capsaicin Derivatives Containing a Sulfonic Acid Esters Moiety - Xie, Dandan; Yang, Zaiping; Hu, Xin; Wen, Yin (Frontiers in Chemistry, 2022)
In order to development efficient and broad-spectrum bactericide, a series of novel capsaicin derivatives containing a sulfonic acid esters moiety was synthesized. The structure of those compounds were confirmed by nuclear Magnetic Resonance Spectroscopy (NMR) and high resolution mass spectrum (HRMS). The results of bioactivities revealed that some target compounds exhibited remark antibacterial activity. Compound 3b exhibited the highest activities against Pseudomonas syringae pv. Actinidiae (Psa), Xanthomonas oryzae pv. Oryzae (Xoo) and Xanthomonas axonopodis pv. Citri (Xac), the values were 86%, 54% and 92% at 50 μg/mL, respectively, which was higher than thiodiazole-copper (87%, 34% and 77%) and bismerthiazol (87%, 37% and 75%). Although some compounds also showed certain activity against spodoptera frugiperda, but it was weaker than positive control monosultap and mulfoxaflor. Thus, bioassay results recommend these newly designed and synthesized scaffolds should be used as a bactericide lead compound rather than a insecticide lead compound.